Hubungan Pengetahuan dan Sikap dengan Konsumsi Sugar-Sweetened Beverages pada Wanita Usia Produktif - Setyanurlia, Anggita Rifky; Sumarmi, Sri (Universitas Airlangga, 2024)
Background: Consumption of sweet drinks, or Sugar-Sweetened Beverages (SSB), is a common habit among people who think that SSB drinks are social drinks. The level of consumption of SSB by women of reproductive age can be influenced by their level of knowledge and attitude toward consuming SSB. If knowledge and attitude are positive towards consumption of SBB and health, then a person will know the quality and quantity of food and drink consumed. Glycemic control is needed to control blood glucose levels based on diet, which includes the type and amount of food and drinks consumed. Objectives: This study aims to analyze the relationship between knowledge and attitudes toward the consumption of Sugar-Sweetened Beverages (SSB) among women of reproductive age in the city of Surabaya Methods: This research is a type of quantitative descriptive research with a cross sectional research design. The research sample consisted of 125 productive-age female respondents aged 18–30 years who were taken by accidental sampling technique. The data collection consisted of the characteristics of the respondents, namely age, education, the respondents' knowledge questionnaire related to SSB consumption, the attitude questionnaire on SSB consumption, and the SQ-FFQ (Semi Quantitative Food Frequency Questionnaire). The collected data were analyzed by statistical analysis using the Chi-Square test to examine the relationship between the independent variables and the dependent variable with a significance level of 95% (α=0.05) Results: The results showed that there was no significant relationship between knowledge (p=0.504) and attitude (p=0.332) and the consumption of Sugar-Sweetened Beverages (SSB). Conclusions: Female respondents of reproductive age have good knowledge, positive attitude towards consumption of Sugary Drinks (SSB), consume low amounts of SSB (<2x per week), average total energy consumption per day, and average sugar consumption per day of SSB consumption that is in accordance with the recommendations. However, some respondents with positive knowledge and attitudes still consumed high amounts of SSB. Knowledge and attitudes are not necessarily the main factors that influence SSB consumption. The determinants of food and beverage selection can be further investigated to determine the supporting factors for SSB consumption.